A biopolymer-based hybrid cation exchanger pectin cerium(IV) iodate: synthesis, characterization, and analytical applications. Issue 1 (2nd January 2016) - Pathania, Deepak; Sharma, Gaurav; Naushad, Mu.; Priya, Vishal
Abstract: Pectin cerium(IV) iodate (PcCeI) and cerium(IV) iodate (CeI) cation ion exchange materials were synthesized via sol–gel methods. The materials were characterized by using Fourier transform infrared spectroscopy, X-ray diffractometer, thermogravimetric analysis, and scanning electron microscopy. The ion exchange capacity (IEC), thermal stability, distribution coefficient ( K d ), and pH titrations were investigated to recognize the cation exchange behavior of the materials. The IEC of pectin-cerium(IV) iodate (PcCeI and cerium(IV) iodate CeI were reported as 1.80 meq/g and 0.92 meq/g, respectively. The higher distribution coefficient values of 250.01 and 219.14 mg/L confirmed the selectivity of pectin-cerium(IV) iodate hybrid ion exchanger for As 3+ and Zn 2+ . The antibacterial activity of synthesized ion exchangers was explored for E. coli bacteria and observed relatively higher for PcCeI as compared to CeI.